12/7h-6/7=1/3

Simple and best practice solution for 12/7h-6/7=1/3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12/7h-6/7=1/3 equation:


h in (-oo:+oo)

(12/7)*h-(6/7) = 1/3 // - 1/3

(12/7)*h-(6/7)-(1/3) = 0

(12/7)*h-6/7-1/3 = 0

12/7*h-25/21 = 0 // + 25/21

12/7*h = 25/21 // : 12/7

h = 25/21/12/7

h = 25/36

h = 25/36

See similar equations:

| 4x-2x=x+12 | | 42j+18-9j=-28 | | 8(x+x)=28 | | -5-2x-9=-4 | | -2(-4+8q)= | | 3(x+1)=1/81 | | 33=-11a+88 | | (-2+sqrt-8)+(5-sqrt-50)= | | 7p-3q-5q= | | 9+6x^2+x^3=0 | | X^2=x^2-6x | | 12.687*10-4= | | -2x+27=-41 | | -13=12b-b-10 | | -15m=300 | | -17a=289 | | 3a+1=-3*6(a-1) | | 2w-0.4=1+1.18w | | 450-90m=-270 | | 3x+8=9x+12 | | 26-13x=-52 | | 553/48x=265 | | -7=7/8k | | 1.5x+2=20 | | (3c-5)(3c-5)= | | -4(y+2)-6y= | | -5x+47=-31 | | -2(y+6)=y+3-(-2y) | | -180=2x+7(5x-12) | | 2x-6=3x+1-x | | -5h=85 | | 11-(-8x)+5x-(-10)= |

Equations solver categories